The Improvement of Civics Education Achievement of Class VII.2 Students at SMP Negeri 17 Kendari Through Think-Pair-Share Type of Cooperative Learning Model - La Halisi (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
This study aimed to improve student learning outcomes in class VII.2 SMP Negeri 17 Kendari in Civics subjects through applying the Think-Pair-Share (TPS) type of cooperative learning model. This type of research is classroom action research which consists of 2 cycles. Each cycle is carried out by the changes to be achieved. Classroom action research procedures are (1) planning, (2) action implementation, (3) observation and evaluation, and (4) reflection—sources of data from students and teachers. The data types are quantitative and qualitative data, through observation sheets and learning outcomes tests. Using teacher and student observation sheets, how to collect data on the implementation of the Think-Pair-Share kind of cooperative learning model. Knowing outcomes data were taken using test sheets. In the second cycle of research, students who scored 70 were 28 people (87.5%) with an average score of 80.94. There was an increase compared to the first cycle of students who scored 70 as many as 14 people (43.75%) with an average score of 60.63. The conclusion is that the learning outcomes of class VII.2 SMP Negeri 17 Kendari in Civics can be improved by applying the Think-Pair-Share (TPS) type of cooperative learning model.